Analysis of Mathematics Communication Skill of Students Grade IX in Quadratic Equation based on their Mathematics Ability - Dassa, Awi; Nasrullah; Hasniati (ARRUS Journal of Mathematics and Applied Science, 2021)
This study aims to know the description of mathematical communication skills in terms of students' mathematics ability in class IX in solving problems on the subject of quadratic equations. The type of research is qualitative research with a descriptive approach. There were 6 research subjects namely two students that have high-ability, two students that has medium-ability, and two students that has low ability. The instruments used in data collection are written tests and interviews. The results showed that subjects with high mathematical abilities were sufficiently able to describe and state problem situations in written or image form properly, were able to use mathematical symbols and terms appropriately and were able to connect algebraic expressions into mathematical ideas. Subjects with moderate mathematical abilities are able to use mathematical symbols and terms appropriately but are less able to describe and state problem situations in written or image form properly and are also less able to connect algebraic expressions to mathematical ideas. Subjects with low mathematical abilities are not able to describe and state problem situations in written or image form properly and correctly, are less able to use mathematical symbols and terms appropriately and have not been able to connect algebraic expressions into mathematical ideas. The results of this study are expected to add insight and improve students' mathematical communication skills, especially in solving math problems related to the application of everyday life.